Acoustical Performance of Palm Oil Clinker Sand Sound Absorber. Issue 1 (July 2020) - Haron, Z; Yahya, K; Galip, N S; Zakaria, M Z; Jahya, Z; Darus, N; Abdullah, R; Din, N C
Abstract: This paper presents the results of a study in which the performance of palm oil clinker (POC) sandas an alternative acoustic material for controlling noise problems was investigated. The specimens were prepared using the basic mortar mixture of cement-to-river sand ratio of 1:4. The five mixtures used in the study containedPOC sand at the amounts of 0%, 25%, 50%, 75% and 100% of the total weight of the sand. Hardened mortar properties of density and compressive strength as well asacousticperformance were measured. The results show that the specimens containing POC sand gave an average noise reduction coefficient of 0.30, which is larger than the corresponding value of 0.25 for the specimens withriver sand only. The combination of 50% POC and 50%river sand achieved the highest sound absorption coefficient of 0.5 at 315 Hz and 0.4 at 1000Hz. It was also found that although POC sand reduced the compressive strength of specimens, the values obtained was still within the strength limit of non-load bearing structures. The findings suggest that POC sand has the potential to be used in the construction of non-structural wall in reducing the noise pollution.